(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2026)
This article relates linguistic risk-taking (LRT) to the context of future language educators. LRT refers to language learners stepping beyond their comfort zones by using a target language in challenging communicative situations—experiences that can lead to personal growth, enjoyment and a sense of accomplishment. While LRT has been recognized as a valuable element in language learning, its role among teacher trainees remains underexplored. Yet, this group is uniquely positioned to influence LRT in their future classrooms, acting as practitioners and role models for their future students. Raising awareness among teacher candidates about the educational and emotional benefits of LRT is important. Choosing a participatory approach, a survey of 81 university students training to become English teachers was conducted. The results reveal insights into their perceptions and preferences of LRT, particularily for tailoring the Canadian LRT initiative to their needs (Slavkov & Séror, 2019) within their learning context.